Current Situation of Korean Studies in Laos - SOMSAMONE, Vilayphone (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
This paper describes the Current Situation of Korean Studies in Laos. Laos is located in Southeast Asia and it is a landlocked country which is largely mountainous, with the most fertile land founded along the Mekong plains. Since the diplomatic relation between the Lao PDR and the Republic of Korea re-established 1995, then the relation of both countries has developed widely and closely at various kinds of trade, investment, tourism and government cooperation. Korean has engaged in major investment in Laos not only in the public sector, but private companies also have a heavy presence in Laos. While people in Laos have a favorable perception of the Korean people and culture due to promotional efforts by the Korean government and business concerns, it seems natural for the Korean Wave to gain considerable popularity in Laos. However, Korean Studies are still an infant stage in Lao PDR, but there has been growing recognition a bout Korean Studies at the Universities. It is quite sure that those efforts will end up creating a solid basis for the future growth of Korean Studies in Laos.